Cystoid macular oedema following cataract surgery: A review. (23rd April 2019) - Han, Jina V.; Patel, Dipika V.; Squirrell, David; McGhee, Charles NJ.
Abstract: Pseudophakic cystoid macular oedema (PCMO) remains a significant cause of compromised postoperative vision in contemporary cataract surgery. Well‐established risk factors include intraoperative complications such as posterior capsule rupture and preoperative factors including: diabetes mellitus, uveitis, retinal vein occlusion, epiretinal membrane. The role of topical glaucoma medications in PCMO continues to be debated. Current treatment strategies largely target suppression of inflammation. Topical NSAIDs remain the mainstay in prophylaxis and treatment of PCMO. Topical corticosteroids are commonly used as monotherapy or in combination with NSAIDs. Unfortunately, high‐quality trials are notably lacking for other PCMO treatment modalities such as: periocular corticosteroids, orbital floor triamcinolone, intravitreal triamcinolone, corticosteroid implants, intravitreal bevacizumab and pars‐plana vitrectomy. A lack of consistency in defining PCMO and resolution of PCMO explains why even large systematic reviews may come to contradictory conclusions. This review explores the varied contemporary evidence‐base in relation to the aetiology, diagnosis, prophylaxis and treatment of PCMO.